EFEKTIVITAS PEMASARAN BANK SYARIAH MENGGUNAKAN MEDIA SOSIAL INSTAGRAM DI INDONESIA” (Studi Kasus pada PT. BNI Syariah) - Indriyani -; Rizal Fahlevi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The purpose of this study is to see the level of marketing effectiveness carried out by Bank BNI Syariah using social media Instagram. The rapid development of Instagram in Indonesia has made Bank Negara Indonesia Syariah actively use this social media as a forum for promotion on Instagram under the account name @ bni.syariah. So it is recorded that as of January 2019 the @ bni.syariah account has the most followers or followers of 37.8 thousand. Then followed by the account @banksyariahmandiri 36.4 thousand followers, @brisyariah 32.5 thousand followers, @ bank.muamalat 25.7 thousands followers, @bankbjbsyariah 8,095 followers, @bankmegasyariah 5,619 followers, @hababankaceh 5,399 followers, @bank_syariahbukopin 2,736 followers, and @ panindubaisyariah.bank 263 followers. Instagram is effectively used as a marketing medium for Islamic banks, especially for BNI Syariah, which is effectively used as a media for promotion and communication media with BNI Syariah customers. With the existence of Instagram as a marketing medium for Islamic banks, in this case BNI Syariah is very helpful in introducing Islamic bank products and helping to increase BNI Syariah revenue itself. Although, currently Instagram social media is only used as a promotional media or the first media for BNI Syariah to introduce Islamic banking products and is also used as a medium of communication with active BNI Syariah customers. So that any complaints or problems, especially related to service, customers can immediately submit complaints to BNI Syariah via Instagram, and problems can be resolved according to the customer's needs.